PENGARUH LATIHAN POWER OTOT TUNGKAI TERHADAP KECEPATAN TENDANGAN SABIT DALAM CABANG OLAHRAGA PENCAK SILAT PADA ATLET PELATDA 143 TAPAK SUCI PUTERA MUHAMMADIYAH KUNINGAN - Iman Solahudin (Indonesian Journal of Education Teaching and Learning (IJETL), 2024)
This study aims to determine the effect of leg muscle power training on sickle kick speed. This type of research is quantitative research with the One Group Pretest and Posttest Design experimental research method. The sample in this study was 12 athletes who actively participated in Pelatda 143 Tapak Suci Putera Muhammadiyah Kuningan. Data analysis to test normality using the Lilliefors test. From the results of statistical data analysis, there was an increase in the average value (mean) of the pretest results of 17.92 and posttest of 24.00 after the treatment was given. Based on the t-test analysis, it was obtained that t count was 14.600 and t table was 2.228 with a significance level of 0.000. The magnitude of the increase in the form of leg muscle power training can be seen from the calculated t-count value of 14.600 which is greater than the t-table of 2.228, namely (14.600 > 2.228) with a significant value of 0.000 which is smaller than 0.05 (sig < 0.05). The results of the research showed that there was a significant increase in sickle kick speed through leg muscle power training in athletes who took part in Pelatda 143 Tapak Suci Putera Muhammadiyah Kuningan.